A língua brasileira de sinais na educação dos surdos - Oliveira, Hilkia Cibelle da Cruz (2018)
This dissertation makes a historical narrative about the course of the creation of sign language in the world and, later, the appearance of the Brazilian Language of Signs (Libras) – Sings languages in Brazil; deals with the communication barrier that prevents the hearing-impaired from developing fully in the various social environments in which they are situated and of the public policies aimed at the development of educational service for the hearing-impaired as a linguistic minority within the regular educational system in Brazil . The aim of this research is to make a bibliographical description of the discussions related to the education of the hearing-impaired and to defend a higher qualification of bilingualism in relation to the special education and their inclusion in the school. With regard to the techniques and procedures used to prepare this monograph, we used the bibliographic method and exploratory-descriptive research, with a qualitative approach. As a result, it was observed that the oral-discursive methodology adapted in the teaching of the hearing-impaired makes the social and communicational barriers insurmountable as the sign language is of total relevance for the construction of the learning of its natives.